Spatiotemporal variability of urinary pesticide biomarker levels in 201 South African children sampled five times over two years - Molomo, Regina Ntsubise; Veludo, Adriana Fernandes; Viglietti, Paola; Wey, Hannah; Petitpierre, Anouk; Lindh, Christian ; 0000-0001-7435-9890; Röösli, Martin; Dalvie, Mohamed Aqiel; Fuhrimann, Samuel (Environment International, 2025)
Background: Understanding pesticide exposure variability over time among children is crucial towards understanding potential acute and long-term health effects of pesticides but data is lacking. Objective: We assessed spatiotemporal and seasonal variability of urinary biomarkers in children at five time points across two years within three agriculturally intensive areas of the Western Cape, South Africa (Grabouw, Piketberg and the Hex River Valley). Methods: A total of 201 children (aged 9–15 years) provided a total of 1005 spot urine samples and completed pesticide exposure-related questionnaires at five time points between 2017 and 2019. Nineteen urinary pesticide biomarkers including organophosphates, pyrethroids, dithiocarbamate and triazoles were analyzed using liquid chromatography tandem mass spectrometry and adjusted for specific gravity. Intraclass correlation coefficients (ICCs) evaluated temporal agreements between repeated urine samples. Linear mixed-effects models assessed the effects of farm residency, study area and pesticide spraying period on urinary pesticides levels. Risks of daily intake of pesticides were estimated using reverse dosimetry. Results: Ten out of fourteen detected biomarkers had a detection frequency above 75%. Levels of 2-isopropyl-4-methyl-6-hydroxypyrimidine (IMPy) (ICC = 0.60) and 3, 5, 6-trichloropyridinol (TCPy; ICC = 0.49) showed moderate and fair temporal agreement between the five sampling points. Children in Grabouw had on average higher biomarker levels compared to the other two areas. Pesticides’ specific spraying periods were associated with an increased TCPy (+32%), IMPy (+79%) and ethylene thiourea (ETU) (+81%) levels compared to non-spraying periods. The estimated daily intakes (EDIs) for most biomarkers were within the acceptable daily intakes (ADIs). However, EDIs exceeded the ADIs in 23.0% of children for TCPy, 8.9% for IMPy, and 0.5% for both 3,5-dichlorophenyl-2-chloroacetic acid (DCCA) and 4-hydroxy-pyrimethanil (OHP). Discussion: High temporal variability and regional exposure contrasts highlight the need for repeated urinary biomarker measurements across locations to accurately assess pesticide exposure for epidemiological studies in rural children. Observed exposure levels exceeding safety thresholds for organophosphates, pyrethroids and triazoles warrant further investigation.
Publisher Copyright: © 2025 The Authors
Keywords: Children; Estimated daily intake; Organophosphates; Pyrethroids; Seasonality; Spatiotemporal; Urinary pesticide biomarkers